2017
DOI: 10.3389/fped.2017.00056
|View full text |Cite
|
Sign up to set email alerts
|

Waiver of Consent in a Trial Intervention Occurring at Birth—How Do Parents Feel?

Abstract: BackgroundWe have previously demonstrated that it is difficult to obtain a representative subject sample when conducting a randomized controlled trial (RCT) at or near the time of birth and obtaining antenatal consent. Waiver of consent has been used in neonatal trials, but parents’ reactions to being enrolled in these trials have never been reported.MethodsThe parents enrolled in a RCT involving a waiver of consent with a post-delivery discussion were asked to take part in a brief survey. The survey questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…This approach has been evaluated in peri-partum research in the CONsent methods in childreN’s emergEncy medicine and urgent Care Trials (CONNECT) study which found that parents and practitioners, while initially expressing concerns about deferred consent in the CATheter infections in CHildren trial (CATCH) trial, later described support for deferred consent in emergency trials to facilitate progress in this area, if the intervention was already in use in routine clinical practice 10. A survey of parents whose babies had participated in a randomised controlled trial evaluating two different methods of placental transfusion to premature infants which involved a deferred consent process reported an overall positive (69%) response to their baby’s involvement 11. ‘Waiver of consent’ describes a different process, whereby informed consent is not a requirement of the study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been evaluated in peri-partum research in the CONsent methods in childreN’s emergEncy medicine and urgent Care Trials (CONNECT) study which found that parents and practitioners, while initially expressing concerns about deferred consent in the CATheter infections in CHildren trial (CATCH) trial, later described support for deferred consent in emergency trials to facilitate progress in this area, if the intervention was already in use in routine clinical practice 10. A survey of parents whose babies had participated in a randomised controlled trial evaluating two different methods of placental transfusion to premature infants which involved a deferred consent process reported an overall positive (69%) response to their baby’s involvement 11. ‘Waiver of consent’ describes a different process, whereby informed consent is not a requirement of the study.…”
Section: Introductionmentioning
confidence: 99%
“…This again presents concerns for patient autonomy and ethically conducted research. Neonatal trials where low-risk interventions or standard of care are being evaluated have employed a waiver of consent; however, parental understanding and acceptance of this has not been evaluated in depth 11…”
Section: Introductionmentioning
confidence: 99%
“…In this study, most parents preferred a prospective consent approach 31. Rich and Katheria, however, suggested that deferring consent for DR studies is acceptable for parents 32. They reported a lack of negative parental reaction on the usage of a deferred consent approach for a specific DR study, although bias may have occurred as all questioned parents agreed for the study participation of their child.…”
Section: Introductionmentioning
confidence: 68%
“…Interviewed providers with first-hand experience with approaching parents for deferred consent suggested that these concerns can be overcome by appropriate communication with parents and timing of the consent procedure. Rich and Katheria37 reported positive parental perceptions with deferred consent, as in the postnatal period there was more time in a non-stressful environment to inform parents about study procedures, allowing parents to truly recall and understand their child being in a DR study. Further studies on parental experiences with deferred consent, including experiences of parents of neonates that passed away or parents that refused deferred consent, may provide insight into the best way to approach parents for deferred consent.…”
Section: Discussionmentioning
confidence: 99%